The effects of self-esteem and influence of friends via social media on body image amongst children - Ahmad, A.; Izian Idris, *; Moy, Regina Li Jing (Sciedu Press, 2019)
Introduction: With the rise and fall of many communication platforms embedded in our everyday lives and the ongoing maturity of the digitalization era, social media usage has tremendously increased over the past decade. The purpose of this research is to identify to what extent self-esteem and the influence of friends" impact children's perception of their body image through social media and how powerful social media in influencing the body image of children. Methodology: The theoretical implication of this study is to expand the usage of the Signalling theory, Sociocultural theory and Social Comparison theory towards better explaining children"s behaviors and the factors that impact children's view of their body image. 282 children were recruited using the snowball sampling technique and data collected were analyzed using Smart-PLS to see the impacts and relationship between all variables. Results: This study found that self-esteem and friends do impact body comparison on social media. However, self-esteem is negatively correlated. The study also identified that there is a significant direct relationship between the direct impacts of self-esteem and friends towards the body image. On the other hand, social media is found to have no direct impact on body image. Conclusion/-and Recommendations: This study provides a better insight for the government on the importance of regulation of advertisements particularly via social media and for the society at large to create a more socially supportive environment for adolescents to communicate and help them grow their mind-set on the acceptable and realistic standards of beauty as well as contributes to the existing knowledge on the role of social media and adds knowledge to how powerful social media in giving impacts to body image among adolescences.